The Economics of Knowledge Regulation: An Empirical Analysis of Knowledge Flows - Carolin Haeussler (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2009)
Successful innovation depends on the management of a firm's knowledge base. This paper empirically investigates the determinants of knowledge regulation. Using a unique survey dataset, the analysis suggests that R&D managers do not leak knowledge randomly, but rather regulate knowledge consciously. We find that the source and the channel of knowledge inflows impact knowledge regulation. The findings reveal that the more a firm profits from knowledge inflows from competitors, the fewer actions it takes to regulate outgoing knowledge. We do not find that the extent of knowledge inflows from collaborating firms impacts knowledge regulation. However, the type of channel being used to acquire knowledge matters. Compared to public channels, the different types of private channels used to access knowledge inflow and the type of the competitive relationship influence the firms' decision to regulate knowledge outflow in the following way: concerning relationships with competitors, firms regulate knowledge outflow more when using formal channels, but less when using informal channels (although a significant difference is not found with the latter); concerning collaborative relationships, firms regulate knowledge outflow less regardless of whether they are using formal or informal private channels compared to using public channels. Presumably firms that acquire knowledge from competing firms through formal private channels compared to public channels, try to establish opaque and soundproof fences to surround them, whereas firms that acquire knowledge from collaborating firms through formal or informal private channels do not want to restrict circulation, but rather facilitate inter-firm knowledge exchange. Our results have important implications for academics and R&D managers alike.
urn:nbn:de:bvb:19-epub-8971-9
Keywords: O32; L21; 650; knowledge management; R&D; biotechnology